Determination of the Antioxidant Capacity of Germinated and Yeast-Fermented Sweet and Bitter Lupin Seeds and Sprouts via Cyclic Voltammetry Compared to the Spectrophotometric and Photochemiluminescence Methods - Danuta Zielińska; Piotr Gulewicz; Małgorzata Kasprowicz-Potocka; Henryk Zieliński (Applied Sciences)
This paper describes the total antioxidant capacity (TAC) of sweet lupin (Lupinus luteus cv. Lord—LLL) and narrow-leaved bitter lupin (Lupinus angustifolius cv. Mirela—LAM) sprouts fermented by yeast, determined by deploying the updated analytical strategy based on three assays. The procedures covered electrochemical, spectrophotometric, and photochemiluminescence methods. Cyclic voltammetry (CV), the scavenging of 2,2-diphenyl-1-picrylhydrazyl radicals (DPPH⦁), and photochemiluminescence (PCL) assays against superoxide anion radicals were applied to hydrophilic (ACW) and lipophilic (ACL) fractions, and the data obtained were used to calculate the TAC after sequence extraction of the samples with 80% methanol followed by methanol/hexane (4:1; v/v). The total polyphenol content (TPC) in the hydrophilic fractions was measured using Folin–Ciocalteu reagent. The fermentation of the LLL and LAM seeds had no impact on the antioxidant capacity of their H fractions, whereas it increased the content of their L fractions up to 56%. The germinated lupin seeds of both cultivars showed slightly increased TAC than the fermented ones. The TPC in the yeast-fermented sprouts was slightly higher compared to the LLL sprouts, about twofold higher than in the fermented LLL seeds, and finally almost fivefold higher compared to the LLL seeds. A beneficial effect of fermentation was found with respect to LAM materials. The TAC of the fermented LLL and LAM sprouts measured via CV and PCL assays was almost twofold higher and eight and six times higher, respectively, compared to the seeds. These findings clearly suggest that the seeds of yellow sweet lupin (Lupinus luteus cv. Lord) are the most suitable for producing fermented sprouts with a high content of electroactive polar compounds able to scavenge multiple free radicals of biological and non-biological origin. The updated analytical strategy for the determination of the total antioxidant capacity proved to be a viable tool for screening processed lupin seeds.